Assessment of safflower for susceptibility to Pythium ultimum, the causal agent of damping-off. - Pahlevani, M.; Ahmadi, A.; Razavi, S. (Plant Breeding and Seed Science, 2010)
Genetic resistance against Pythium species would be an efficient control of this major seed and seedling fungal pathogen in safflower (Carthamus tinctorius), but so far no source has been identified. Therefore, identifying and then incorporating genetic resistance into the cultivars would be an ideal method of control for this disease. So in this study the resistance to seed rot and damping-off caused by Pythium ultimum among seventeen genotypes of safflower collected from all major production regions of the crop in Iran and some other countries was investigated. Pythium ultimum, previously identified as the most prevalent Pythium isolates on safflower, were used to infest the sterilized soil, which was seeded with safflower genotypes in greenhouse conditions. The experiment was conducted as a split plot design in which sterile and Pythium-infested soils were considered as main plots, and seventeen genotypes of safflower were sub plots. In sterile media, percent of seedling emergence (SES) and in Pythium-infested media, percent of seedling emergence (SEI), percent of diseased seedlings (DSI), percent of uninfected seedlings (USI) and percent of non-emerged seeds (NSI) were recorded. Symptoms showed that in safflower, damping-off occurred in both forms of pre and post emergence. Genotypic variation was existed for level of susceptibility to P. ultimum. Significant differences in SES and SEI were detected among safflower genotypes (P < 0.01), and a significant correlation between SES and seed weight (P < 0.05); SES with SEI (P < 0.05) were detected. Result showed that between evaluated genotypes there wasn’t any genotype with complete resistance (100%) to P. ultimum, so the susceptibilities were assayed. Based on the assessed variables, genotypes LRV-55-295, Aceteria, PI-250537 and IL-111 appear to be highly susceptible to the Pythium infection, whereas 34040, Arak281, and Isfahan were the least susceptible to the disease. Further research will be conducted to determine whether the resistance detected in these genotypes is heritable...